الظواهر الصوتية في كتابي بانيني وسيبويه دراسة مقارنة: The Book of Panini and the Book of Sībawayh: A Comparative Study - شير على خان (الدراسات الإسلامية, 2020)
The article deals with the works of two celebrated ancient linguists i.e., Panini, an Indian linguist (fl. ca. 500 BCE) and Sībawayh, an Arab linguist and grammarian (d. 996 CE). It elaborates the importance of the book of Panini titled Ashtadhyayi and the book of Sībawayh al-Kitab. Both the books are authentic sources of linguistics, phonetics, phonology, morphology, syntax, semantics, and lexicon as well as of the language spoken at the time of their compilation. The article, however, focuses only on the matters relating to phonetics and phonology in both the books in order to find out similarities and differences between them.